Forming of national model of corporate social responsibility - Kuzheliev, Mykhailo (Skhid, 2013)
The article reviews a historic and transformational aspects of the national model of corporate social responsibility and the main trends of its development, provides the main approaches to the formation of a national model of CSR that will improve the level of corporate culture in society